Removal of Organic and Nutrients in Young Leachate Using Combined Anaerobic/Anoxic/Aerobic Attachedgrowth Bioreactor - Movahed, Bahareh Sanaie (2009)
The study was conducted to evaluate the biological nutrient removal of young leachate from transfer station that is considered as a high concentration wastewater due to high chemical oxygen demand (COD) and biological oxygen demand (BOD) content. The process has been performed in the combined anaerobic/anoxic/aerobic bioreactor. Biological nitrification and denitrification in combination with phosphorous removal have been shown appropriate to remove nitrogen and phosphorous in this single column bioreactor where Cosmo-ball media were launched into the aerobic zone to improve bacteria growth in this zone. The anaerobic and aerobic acclimatized liquor seeded into the anaerobic and aerobic zone of bioreactor respectively and after 30 days of transition period, experimental procedure was started in two different phase. The diluted leachate injected to the up flow continuous anaerobic/anoxic/aerobic vertical reactor in process of two phases which each phase consist of three runs. The first phase involved three different organic loading rates (OLR) of 8, 13.3 and 26.6 kg COD/ m3.day with constant 24 hour of hydraulic retention time (HRT). In the second phase three different HRT of 12, 24, and 36 hours; and constant OLR (=13.3 kg COD/ m3.day) applied to the process to find out the best organic removal. Ammonical nitrogen removal investigated under different C/N ratio in the first phase and in the second phase were studied under different HRT. Phosphorous removal was examined in different concentrations due to leachate dilution in both phases. This experiment performed in the Environmental and Chemical UPM laboratory and samples were collected from the Taman Beringin Municipal Solid Waste Transfer Station, Klang, Selangor. The results showed that, the highest removal of ammonical nitrogen in aerobic run was due to the presence of sufficient amount of oxygen. The results of the project indicated that by increasing C/N ratios, ammonia removal decreased due to the competition between autotroph and heterotroph microorganisms which was 85% in the lowest organic concentration. The results indicated as HRT increased, NH4-N concentration of effluent decreased and the removal efficiency increased accordingly and the best removal efficiency of the system were achieved in 36 hour as much as 89%. The best organic removal were obtained at the lowest COD loading rate and the longest HRT in phase one and two which was equal to 92% and 94% respectively. It was found that the anaerobic/anoxic/aerobic attached bioreactor with Cosmo-Ball as the media with significant acclimatizing and transition period for bacteria growth has succeeded in removing nitrogen and organic from diluted young leachate with high amount of COD and low amount of nitrogen.